2002
DOI: 10.1097/00005237-200212000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Perinatal Outcomes in Mexican Immigrant Childbearing Women

Abstract: Despite several sociocultural factors associated with increased risk for low birth weight and infant mortality, the rate for infants born to first-generation and less acculturated Mexican immigrant women is the same as that of non-Hispanic whites, and half that of African Americans with similar risks. It appears that sociocultural rather than genetic variables are the primary factors associated with this phenomenon. Higher levels of acculturation to North American values and lifestyle in Mexican American child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 68 publications
6
67
0
6
Order By: Relevance
“…The effect is the "cleanest" in Mexican American women. Among Mexican American women, acculturation is associated with lower birth weight (19,22,27,56,129,132,156), prematurity (22,35,156), and teenage (<17 years) births (29). Cobas found that acculturation appears to affect LBW status indirectly through smoking and dietary intake (27).…”
Section: Illicit Drug Usementioning
confidence: 99%
“…The effect is the "cleanest" in Mexican American women. Among Mexican American women, acculturation is associated with lower birth weight (19,22,27,56,129,132,156), prematurity (22,35,156), and teenage (<17 years) births (29). Cobas found that acculturation appears to affect LBW status indirectly through smoking and dietary intake (27).…”
Section: Illicit Drug Usementioning
confidence: 99%
“…Ve zkoumaných studiích, které tak činí, je migrace vymezena základním pohybem směřujícím k překročení národních hranic [Essén 2001;Quintanilha et al 2016;Urquia et al 2010a] a je charakterizována jako tranzice [Callister, Birkhead 2002;Collins, Zimmerman, Howard 2011;Zeitlin et al 2004]. Popřípadě ji výzkumníci rozlišují podle příčin a motivací [Adanu, Johnson 2009;Balaam et al 2013;Janevic, Savitz, Janevic 2011].…”
Section: Migrace Jako Tranziceunclassified
“…13 Výzku-my určují hranice dostatečně dlouhé doby akulturace osob různě. Mělo by se jednat o "dosti dlouhé období" [Callister, Birkhead 2002], které například Zambrana et al [1997] specifikuje jako období delší než 10 let. Délka pobytu může také ovlivnit zařazení ženy do kategorie imigrantek.…”
Section: Migrace Jako Tranziceunclassified
See 2 more Smart Citations